Indigenous and non-Indigenous people experiencing homelessness and mental illness in two Canadian cities: A retrospective analysis and implications for culturally informed action - Brittany Bingham; Akm Moniruzzaman; Michelle Patterson; Jino Distasio; Jitender Sareen; John O’Neil; Julian M Somers (BMJ Open)
Objectives Indigenous people in Canada are not only over-represented among the homeless population but their pathways to homelessness may differ from those of non-Indigenous people. This study investigated the history and current status of Indigenous and non-Indigenous people experiencing homelessness and mental illness. We hypothesised that compared with non-Indigenous people, those who are Indigenous would demonstrate histories of displacement earlier in life, higher rates of trauma and self-medication with alcohol and other substances.Design and setting Retrospective data were collected from a sample recruited through referral from diverse social and health agencies in Winnipeg and Vancouver.Participants Eligibility included being 19 years or older, current mental disorder and homelessness.Measures Data were collected via interviews, using questionnaires, on sociodemographics (eg, age, ethnicity, education), mental illness, substance use, physical health, service use and quality of life. Univariate and multivariable models were used to model the association between Indigenous ethnicity and dependent variables.Results A total of 1010 people met the inclusion criteria, of whom 439 self-identified as Indigenous. In adjusted models, Indigenous ethnicity was independently associated with being homeless at a younger age, having a lifetime duration of homelessness longer than 3 years, post-traumatic stress disorder, less severe mental disorder, alcohol dependence, more severe substance use in the past month and infectious disease. Indigenous participants were also nearly twice as likely as others (47% vs 25%) to have children younger than 18 years.Conclusions Among Canadians who are homeless and mentally ill, those who are Indigenous have distinct histories and current needs that are consistent with the legacy of colonisation. Responses to Indigenous homelessness must be developed within the context of reconciliation between Indigenous and non-Indigenous Canadians, addressing trauma, substance use and family separations.Trial registration number ISRCTN42520374, ISRCTN57595077, ISRCTN66721740.